Market Power and Welfare in Asymmetric Divisible Good Auctions - Carolina Manzano; Xavier Vives (Center for Economic Studies and ifo Institute (CESifo), 2016)
We analyze a divisible good uniform-price auction that features two groups each with a finite number of identical bidders. Equilibrium is unique, and the relative market power of a group increases with the precision of its private information but declines with its transaction costs. In line with empirical evidence, we find that an increase in transaction costs and/or a decrease in the precision of a bidding group.s information induces a strategic response from the other group, which thereafter attenuates its response to both private information and prices. A “stronger” bidding group -which has more precise private information, faces lower transaction costs, and is more oligopsonistic- has more market power and so will behave competitively only if it receives a higher per capita subsidy rate. When the strong group values the asset no less than the weak group, the expected deadweight loss increases with the quantity auctioned and also with the degree of payoff asymmetries. Market power and the deadweight loss may be negatively associated.
Keywords: D44; D82; G14; E58; 330; demand/supply schedule competition; private information; liquidity auctions; treasury auctions; electricity auctions